Industrial-Scale bioprocess simulation of polyphenol production using superpro designer (2021)
Polyphenols are molecules with antioxidant potential for several diseases. In this research, an analysis of polyphenols production costs from Theobroma cacao L suspension cell culture was evaluated. The latter proposing different scenarios based on a large-scale plant production using the SuperPro Designer software. Two strategies for bioprocess improvement were proposed based on information from a traditional suspension cell culture (Strategy I). These improvements are firstly based on adding elicitors (Strategy II) for increasing polyphenol production and secondly, energetic use of cane bagasse and rice bran (Strategy III) by adding a gasifier. Results showed that the percentage of losses decreases from 19 % to only 5.8 % applying a recirculation system in losses lines product regarding Strategy II. Also, adding Methyl Jasmonate (MJ) elicitor increased the Y p / s yield up to 0.08 kg polyphenols/kg glucose. Gasification proposed in Strategy III achieved supplying 37 % of energy requirements using only 1.14 % of bagasse. One essential finding refers to the decreased cost of producing a 100 mg tablet formulated at 50 % of the active substance. Therefore, the latter resulted in 0.23 USD / tablet: promising data compared to 1.0-2.0 USD / tablet corresponding to the average value in the market. Thus, this research demonstrates that the increase of polyphenols by adding elicitors positively influences the operating costs.